Hubungan Antara Motivasi Belajar Peserta Didik Dengan Cara Penyampaian Guru Di Madrasah Tsanawiyah Serpong MTS Kecamatan Serpong Kota Tangerang Selatan - Dewi Ratnasari (Journal Innovation In Education, 2024)
Every human being has needs in life, every need demands to be fulfilled no matter what the circumstances. For example, someone who is hungry, even at night, will definitely crawl or sneak around looking for food. Why is that because hunger is a necessity for life that is very important for the continuation of life in the future. Various human needs demand to be fulfilled so that people feel satisfied. So if he is hungry and gets food then he will feel satisfied. Nowadays, teaching is considered equal and synonymous with active student learning. Teaching is seen as a system consisting of components that depend on each other, and are organized between competencies that must be achieved by students, subject matter, language subjects, teaching methods and approaches, teaching media, learning resources, class organization, and assessment.